IFITM3 affects the level of antibody response after influenza vaccination - Na Lei; Yan Li; Qiang Sun; Jian Lu; Jianfang Zhou; Zi Li; Liqi Liu; Junfeng Guo; Kun Qin; Haibin Wang; Jianhong Zhao; Chong Li; et al. (Emerging Microbes and Infections)
Interferon-induced transmembrane protein 3 (IFITM3) as an antiviral factor can inhibit replication of several viruses including influenza virus. A single-nucleotide polymorphism rs12252-C of IFITM3 results in a truncated IFITM3 protein lacking its first 21 amino acids, which is much higher in the Han Chinese population and associated with severe illness in adults infected with pandemic influenza H1N1/09 virus. To investigate if IFITM3 or IFITM3 rs12252-C could affect the antibody response after influenza vaccination, we detected the haemagglutination inhibition (HI) of 171 healthy young adult volunteers (IFITM3 rs12252-C/C, C/T, T/T carriers) and in an IFITM3-deletion mouse model (Ifitm3-/-) after trivalent inactivated vaccine (TIV) immunization. Seroconversion rates for H1N1, H3N2 and B viruses in IFITM3 rs12252-C/C genotype carriers was lower compared with C/T and T/T donors. Significantly lower levels of specific antibodies to H1N1, H3N2 and B viruses and total IgG were observed in Ifitm3-/- mice. Correspondingly, the numbers of splenic germinal centre (GC) B cells, plasma cells, TIV-specific IgG+ antibody secreting cells and T follicular helper cells in Ifitm3-/- mice were lower compared with wild type mice. However, the number of memory B cells was higher in Ifitm3-/- mice at day 7 after booster. The HI level of Ifitm3-/- mice remained lower than WT mice after third vaccination. Moreover, the transcriptional network regulating GC B cell and plasma cell differentiation was abnormal in Ifitm3-/- mice. Our results indicate that IFITM3 deletion attenuated the antibody response. The mechanism of influenza-IFITM3 interactions affecting the antibody response requires further investigation.